Comparing a mercury optical lattice clock with microwave and optical frequency standards. (2nd November 2016) - Tyumenev, R; Favier, M; Bilicki, S; Bookjans, E; Targat, R Le; Lodewyck, J; Nicolodi, D; Coq, Y Le; Abgrall, M; Guéna, J; Sarlo, L De; Bize, S
Abstract: In this paper we report the evaluation of an optical lattice clock based on neutral mercury with a relative uncertainty of 1.7 × 10 − 16 . Comparing this characterized frequency standard to a 133 Cs atomic fountain we determine the absolute frequency of the 1 S 0 → 3 P 0 transition of 199 Hg as ν Hg = 1128 575 290 808 154.62 Hz ± 0.19 Hz ( statistical ) ± 0.38 Hz (systematic), limited solely by the realization of the SI second. Furthermore, by comparing the mercury optical lattice clock to a 87 Rb atomic fountain, we determine for the first time to our knowledge the ratio between the 199 Hg clock transition and the 87 Rb ground state hyperfine transition. Finally we present a direct optical to optical measurement of the 199 Hg/ 87 Sr frequency ratio. The obtained value of ν Hg / ν Sr = 2.629 314 209 898 909 15 with a fractional uncertainty of 1.8 × 10 − 16 is in excellent agreement with a similar measurement obtained by Yamanaka et al (2015 Phys. Rev. Lett. 114 230801 ). This makes this frequency ratio one of the few physical quantities agreed upon by different laboratories to this level of uncertainty. Frequency ratio measurements of the kind reported in this paper have a strong impact for frequency metrology and fundamental physics as they can be used to monitor putative variations of fundamental constants.